2014
DOI: 10.1186/s12968-014-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution cardiovascular magnetic resonance diffusion tensor map from ex-vivo C57BL/6 murine hearts

Abstract: BackgroundThe complex cardiac fiber structural organization and spatial arrangement of cardiomyocytes in laminar sheetlets contributes greatly to cardiac functional and contractile ejection patterns. This study presents the first comprehensive, ultra-high resolution, fully quantitative statistical tensor map of the fixed murine heart at isotropic resolution of 43 μm using diffusion tensor (DT) cardiovascular magnetic resonance (CMR).MethodsImaging was completed in approximately 12 hours using a six-directional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
(134 reference statements)
5
18
0
Order By: Relevance
“…Larger pore sizes relative to a previous study were specified to account for the higher ADC and lower FA in cardiac tissue relative to brain white matter. 12 We report values comparable to ex vivo mouse and rat cardiac data reported in the literature, where mean ADC ranged from 0.57-0.89 3 10 -3 mm 2 /s, and FA ranged from 0.25-0.40, 16,17 and show the stability of these measurements over 4 months. 18 We assessed the geometry of the fiber strips based on their nominal thickness and measured mean helix angle, and found that the effective radii of curvature of the inner, middle, and outer strips were 273 mm, 4.88 mm, and 526 mm, respectively.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Larger pore sizes relative to a previous study were specified to account for the higher ADC and lower FA in cardiac tissue relative to brain white matter. 12 We report values comparable to ex vivo mouse and rat cardiac data reported in the literature, where mean ADC ranged from 0.57-0.89 3 10 -3 mm 2 /s, and FA ranged from 0.25-0.40, 16,17 and show the stability of these measurements over 4 months. 18 We assessed the geometry of the fiber strips based on their nominal thickness and measured mean helix angle, and found that the effective radii of curvature of the inner, middle, and outer strips were 273 mm, 4.88 mm, and 526 mm, respectively.…”
Section: Discussionsupporting
confidence: 68%
“…Examples include high-resolution DTI in mouse hearts. 17 and diffusion spectrum imaging in infarcted rat hearts 20 The design of a phantom needs to balance mimicking biological structure, reproducibility in manufacture, and amenability to characterization and validation. On the one hand, it could be argued that the phantom should recapitulate the branching syncytium and discrete sheet arrangement found in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…1. The complex structural organization of cardiac fibers and the spatial arrangement of cardiomyocytes in laminar sheetlets significantly contribute to cardiac function and contractile ejection patterns [14]. Indirect estimation of local cardiac fiber orientation using the procedure of mapping the cardiac fiber from DTI data has been done by MRI and ultrasound [16, 46, 47].…”
Section: Cardiac Fiber and Heart Failurementioning
confidence: 99%
“…Some animal models that have been used with these imaging protocols for HF studies are rat [76, 77], canine [2, 10, 50, 78, 79], rabbit [12, 80], pig [81], sheep [56, 80, 82], and mice [14, 83]. Figure 3 shows representative DT-MRI images of hearts from a mouse, a rabbit, and a sheep.…”
Section: Overview Of Imaging Technologies For Detecting Heart Failurementioning
confidence: 99%
See 1 more Smart Citation